PENGARUH SISTEM PELAYANAN DAN OPERASIONAL PEGADAIAN SYARI’AH TERHADAP JUMLAH PINJAMAN NASABAH DI PEGADAIAN SYARI’AH KOTA PADANGSIDIMPUAN - Rosnani Siregar (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2017)
Sharia Pawnshop stood in 2003. Sharia Pawnshop is standing along with the development of other sharia banks. During the period from its inception until now the final year of 2008 certainly has a pretty good development. Theoretically this development is possible because of their good service to customers. The definition of pawn business in general is the activity of guaranteeing valuables to certain parties (in this case Perum Pegadaian) in order to obtain some money, and the guaranteed goods can be redeemed in accordance with the agreement between the customer with the pawnshop institution. Method of research analysis used in determining the results of this first hypothesis are descriptive, the second hypothesis is descriptive, the third hypothesis is descriptive, the fourth hypothesis is descriptive, the fifth and sixth hypotheses are by weber cambboan based on statistical data through simple correlation. Descriptive means, the author seeks to describe data and facts in a comparative manner. There is a mutual influence between service system and operational system of Perum Pegadaian Syari'ah Alaman Bolak Kota Padangsidimpuan towards the amount of loan turnover loaned to the customer